RESPONSABILIDAD SOCIAL EMPRESARIAL EN LA PEQUEÑA Y MICRO EMPRESA - Freyre Valladolid, Mayela (2005)
The aim of this assessment was to analyze the social responsibility concept applied to both micro and small companies because of limits and managerial practices and thus determine the linkage with sustainable development. The bibliography referred to the analysis and settlement of the socially responsible behaviorism of enterprises, and companies and Universities was reviewed. However the reaffirmation arises in which Social Responsibility Management is still incipient regardless the size or nature of companies. Labor legislation is one of the most injurious when to international agreements is concerned; labor rights are no longer guarantied on the entrepreneur practice. When to environmental legislation is concerned, it is applied only to the medium and large enterprises having information asymmetry. On the other hand population has no collective conscious for consumption so there’s is a social pressure on manage social responsibility in this context In this country micro and small enterprises become a main motor for companies by by creating labor and income conditions for the poorest and thus become social agents on participative processes. There is a conclusion that Management social responsibility on micro and small companies has no implication when to environmental, social standards, are concerned.